GENETIC ENHANCEMENT OF SEMI-EXOTIC MAIZE GERMPLASM - FILHO, JOSÉ BRANCO MIRANDA; REIS, EDÉSIO FIALHO (International Journal of Maize & Sorghum, 2016)
ABSTRACT - The characterization of 26 populations with varying levels of exotic germplasm was conducted in two environments representing distinct locations and planting seasons. The whole set was identified by five subsets: I ≡ local adapted germplasm; II ≡ exotic derived from tropical germplasm; III ≡ semi-exotic derived from tropical germplasm; IV ≡ semi-exotic derived from varying proportion of tropical and temperate germplasm; and V ≡ semi-exotic derived from temperate germplasm. In the experiment εI (Anhembi, SP; three replications) the mean yield (EW - ear weight, t ha-1) for the five sets were 9.49, 8.88, 9.11, 8.68 and 8.51; which are equivalent to 79.5, 74.4, 76.3, 72.7 and 71.3 in percent of the hybrid check. Means for other traits (E10 – weight of ten ears, EL – ear length, ED – ear diameter, and TB – tassel branch number) were also shown. In the experiment εII (Piracicaba, SP; no replications), the following traits were evaluated: EW, GW (grain weight), GR (grain yield ratio), MF (days to male flowering), and SW (specific weight). A low correlation (0.220) was observed for EW between environments. In general, the populations under study presented a fairly good potential to be used in breeding programs. Key words: exotic germplasm, population improvement, Zea mays. SOBRELEVAÇÃO DO VALOR GENÉTICO DE GERMOPLASMA SEMIEXÓTICO DE MILHO RESUMO - A caracterização de 26 populações com vários níveis de germoplasma exótico foi conduzida em dois ambientes, representando locais e épocas de plantio distintas. O conjunto total foi identificado por cinco subconjun-tos: I ≡ germoplasma local adaptado; II ≡ exótico derivado de germoplasma tropical; III ≡ semiexótico derivado de germoplasma tropical; IV ≡ semiexótico derivado de variadas proporções de germoplasma tropical e temperado; e V ≡ semiexótico derivado de germoplasma temperado. No experimento εI (Anhembi, SP; três repetições), as médias de produção (EW – peso de espigas, t ha-1) para os cinco subconjuntos foram 9,49, 8,88, 9,11, 8,68 e 8,51, que são equivalentes a 79,5%, 74,4%, 76,3%, 72,7% e 71,3% da média da testemunha. As médias de outros caracteres (E10 – peso de 10 espigas, EL – comprimento da espiga, ED – diâmetro da espiga e TB – número de ramificações do pendão) também foram apresentadas. No experimento εII (Piracicaba, SP; sem repetição), foram avaliados os caracteres: EW; GW (peso de grãos); GR (rendimento de grãos); MF (dias para florescimento masculino); e SW (peso específico). Uma baixa correlação (0.220) foi observada para EW entre ambientes. As populações avaliadas apresentam bom potencial para serem usadas em programas de melhoramento. Palavras chave: germoplasma exótico, melhoramento de populações, Zea mays.